The effect of dietary patterns on mild cognitive impairment and dementia incidence among community-dwelling older adults - Malek Rivan, Nurul Fatin; Shahar, Suzana; Fakhruddin, Nik Nur Izzati Nik Mohd; You, Yee Xing; Che Din, Normah; Rajikan, Roslee (Frontiers in Nutrition, 2022)
Multiple studies have shown that dietary patterns have beneficial health effects on cognitive function. However, information on this relationship is presently limited, particularly among older adults. Thus, this study aimed to determine the effects of dietary patterns on mild cognitive impairment (MCI) and dementia incidence among Malaysian community-dwelling older adults. In this prospective cohort study, a total of 280 participants aged 60 years and above were included in the five years follow-up analysis. Participants’ socio-demographic, medical history, anthropometry, blood pressure, body composition, biochemical indices, cognitive assessments, psychosocial functions, functional status and dietary intake were obtained. MCI was classified based on Petersen criteria, whilst dementia status was assessed using clinical dementia rating (CDR). Univariate analysis was performed for all variables, followed by multinomial regression analysis to identify the ability of dietary patterns in predicting the incidence of MCI and dementia. After controlling for confounding factors, the findings indicated that ‘local snacks-fish and seafood-high salt foods’ dietary pattern was associated with increased risk of MCI incidence, where the T3 [Adjusted OR=3.943 (95% CI: 1.212 – 12.832), p=0.032] had the highest OR compared to T2 [Adjusted OR=3.252 (95% CI: 1.108 – 9.546), p=0.023]. Meanwhile, a negative association across the tertiles of tropical fruits-oats dietary pattern and dementia incidence was observed (T2: Adjusted OR=0.152 (95% CI: 0.026 – 0.871), p=0.034; T3: Adjusted OR=0.101 (95% CI: 0.011 – 0.967), p=0.047). In conclusion, specific dietary patterns, particularly ‘local snacks-fish and seafoods-high salt foods’, were shown to increase the risk of MCI, while increasing intakes of ‘tropical fruits-oats’ dietary patterns would protect against the dementia incidence among Malaysian older adults.